Internationalization and Firm Risk: An Upstream-Downstream Hypothesis - Kwok, Chuck C. Y.; Reeb, David M. (Journal of International Business Studies, 2000)
Corporate international diversification theory posits that multinational corporations (MNCs) should have lower risk and higher financial leverage than purely domestic corporations (DCs). We suggest an alternative upstream-downstream hypothesis according to which the overall effect of internationalization on the risk and leverage of MNCs is expected to vary with home and target market conditions. The empirical results are consistent with the suggested hypothesis.